Risk Factors for Adverse Maternal and Fetal Outcomes in Women With Confirmed aPL Positivity: Results From a Multicenter Study of 283 Pregnancies - Fredi, Micaela; Andreoli, Laura; Aggogeri, Elena; Bettiga, Elisa; Lazzaroni, Maria Grazia; Le Guern, Véronique; Lojacono, Andrea; Morel, Nathalie; Piette, Jean Charles; Zatti, Sonia; Costedoat-Chalumeau, Nathalie; Tincani, Angela (Frontiers in Immunology, 2018)
Objective: Antiphospholipid antibodies positivity (aPL) is considered as a risk factor for adverse pregnancy outcome (APO). The aim of this study was to determine the risk factors for APO in patients with confirmed aPL positivity, isolated (aPL carriers) or associated with a definite primary antiphospholipid syndrome (PAPS). Methods: The clinical and laboratory features of 283 pregnancies occurring between 2000 and 2014 in 200 women were collected in 3 Institutions. Results: The rate of live birth was 87.9% and APO was observed in 50 cases (17.7%). Multivariate analysis showed that the independent variables related to APO were the concomitant diagnosis of an organ specific autoimmune disease (p=0.012, OR3.29; CI95% 1.29-8.38) and the presence of low complement levels during the first trimester (p=0.02, OR2.3; CI95% 1.17-9.15). No statistical differences were found in APO occurrence among patients treated with low-dose aspirin (LDA) versus those treated with LDA plus heparin (LMWH), but LDA+LMWH was more frequently administered in patients with triple aPL positivity (p=0.001, OR3.21, CI95% 1.48-7.11) and with PAPS (p<0.001, OR8.08, CI95% 4.3-15.4). Based on clinical history, the patients were divided into 4 groups: obstetric, thrombotic, non-criteria APS (clinical non-criteria) and aPL carriers. APO were more frequent in the thrombotic group (24%). Seven patients had a thrombotic event during pregnancy or puerperium (2.4%). Conclusion: Maternal and fetal complications were observed in some aPL positive patients despite their efficient management according to the latest recommendations. Higher risk of an adverse pregnancy outcome was observed in patients with a previous thrombosis and/or more complex autoimmune phenotype.